Get the Story Straight: Contextual Repetition Promotes Word Learning from Storybooks - Horst, Jessica S.; Parsons, Kelly L.; Bryan, Natasha M. (Frontiers in Psychology, 2011)
Although reading storybooks to preschool children is a common activity believed to improve language skills, how children learn new vocabulary from being to has been largely neglected in the shared storybook reading literature. The current study systematically explores the effects of repeatedly reading the same storybooks on both young children's fast and slow mapping ability. Specially created storybooks were read to 3-year-old children three times during the course of one week. Each of the nine storybooks contained two novel word-object pairs. At each session, children either heard three different stories with the same two novel name-object pairs or the same story three times. All children heard each novel name the same number of times. A four-alternative forced-choice task with pictures of the objects was used to test both immediate recall and retention. Children who heard the same stories repeatedly were very accurate on both the immediate recall and retention tasks. In contrast, children who heard different stories were only accurate on immediate recall during the last two sessions and failed to learn any of the new words. Overall, then, we found a dramatic increase in children’s ability to both recall and retain novel word-object associations encountered during shared storybook reading when they heard the same stories multiple times in succession. Results are discussed in terms of contextual cueing effects observed in other cognitive domains.